Successful percutaneous management of occluded ”woven” coronary artery: a case report - Tasal, Abdurrahman; Bacaksiz, Ahmet; Erdogan, Ercan; Küçükdurmaz, Zekeriya (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
“Woven” coronary artery is an uncommon anomaly characterized by the branching of a major epicardial artery into thin channels, which then merge again in order to form the main lumen. Although it is accepted as a benign condition, reduced coronary blood flow and increased shear stress in the narrow braid segments may accelerate atherosclerosis and predispose to the formation of intracoronary thrombus. We describe a 60-year-old man with “woven” left anterior descending and circumflex (Cx) arteries. He had ischemic symptoms due to occlusion in the woven Cx and percutaneous coronary intervention was performed successfully.